Summer field reports, 1995, Jim Dinsmore - Dinsmore, James J.et al (1995)
An annotated list of birds sighted by Jim Dinsmore and others. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of summer 1995. Epson - sheet feed/flatbed